Pressure-holding transfer and testing techniques for natural gas hydrate reservoir core: a brief review - Gao, Qiaoling; Chen, Jiawang; Nan, Liwen; Shen, Jiayi (Frontiers in Marine Science, 2025)
Uncovering the dynamic evolution mechanism of natural gas hydrate reservoir properties is crucial for realizing efficient resource exploration and safe trial mining. Obtaining high-quality hydrate reservoir cores and conducting comprehensive testing and analysis are important prerequisites for obtaining real information about hydrate reservoir. Pressure-holding transfer and testing of natural gas hydrate reservoir cores is a powerful means of accumulating in situ physical analysis data. This report summarizes the current state of development of pressure-holding transfer and testing techniques for natural gas hydrate reservoir cores from both research and application aspects. The advantages and disadvantages of existing gas hydrate reservoir core pressure-holding transfer and testing systems are comprehensively reviewed. The basic methods of pressure core processing, including buckling decomposition, permeability measurement, triaxial testing and integrated measurement, are analyzed, as well as the advantages and disadvantages of these methods. These reviews not only help researchers to better understand the current status of pressure-holding transfer and testing techniques for natural gas hydrate reservoir cores, but also have important reference significance for the in-depth development of future hydrate reservoir core testing technology.